The effect of healthy pregnant plasma and preeclamptic plasma on the phagocytosis index of neutrophil granulocytes and monocytes of nonpregnant women - Rudolf Lampé; Ágnes Kövér; Sándor Szűcs; László Pál; Ervin Árnyas; Robert Póka (Taylor & Francis Group, 2017)
Objective: Phagocyte function of neutrophil granulocytes and monocytes is decreased in healthy pregnancy and further decreased in preeclampsia. The cause of the declined function is unknown. Decreased phagocyte function can lead to the higher infection rate in healthy pregnancy and may also be responsible for the increased susceptibility to infections and high trophoblast concentration in preeclampsia. The aim of this study is to examine the phagocyte function of neutrophil granulocytes and monocytes. Methods: Monocytes and neutrophil granulocytes were separated from the peripheral circulation of six nonpregnant patients and incubated in plasma samples from six healthy pregnant, six preeclamptic pregnant, and six nonpregnant patients. The cells were marked and evaluated for the phagocytosis index with immunofluorescent microscope after phagocyting the zymosan molecules. Results: Phagocyte function of neutrophils as well as monocytes from nonpregnant patients were decreased significantly when the cells were incubated in plasma samples from healthy pregnant patients, and further decreased when incubated in plasma samples from preeclamptic pregnant women. Conclusion: The decreased phagocyte function of neutrophil granulocytes and that of monocytes in healthy pregnancy and the further decreased phagocyte function in preeclampsia is caused by factor(s) in the maternal circulation.